Considering the Social Action within Preaching: Reading 1 Samuel 3 through the Lens of G. H. Mead and H. R. Niebuhr (Homiletic, 2021)
This essay proposes a method to both analyze and create social action within the sermon and examines the process through the narrative example of Samuel’s calling in 1 Samuel 3. The method derives from George H. Mead’s sociological development theory regarding the self’s emergence within a social context, in conjunction with the qualities of radical monotheistic faith outlined by H. Richard Niebuhr. In using their scholarship, we discover how the social action occurring between Samuel, Eli, and God solidifies, shifts, deconstructs, or creates categories of understanding. When preachers pay attention to these realities, they are not only equipped to study the logistics of their sermons but are challenged to strive for an ecological interconnectivity that moves beyond the discursive into the transformative.